Clinical Case of Cellular rejection after Heart Transplantation - Fedkiv, S. V.; Potashev, S. V.; Rudenko, K. V.; Zakharova, V. P.; Chizhevskaya, E. A. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Transplant rejection is one of the most important complications after organ transplantation. It was the main obstacle during the first years after heart transplantation implementation. Wide clinical spread of heart transplantation induced rapid development and implementation of many new immunosuppressants. Further success in this field was due to the use of immunosuppressant combinations which allowed to significantly decrease the incidence of cellular heart transplant rejection. Apoptosis has been implicated in the pathophysiology of various forms of heart disorders. Acute cellular rejection (ACR) causes post-heart transplantation morbidity; invasive techniques are needed for its diagnosis, however, these are not generally available. Endomyocardial biopsy (EMB) is a routine procedure aimed to monitor transplanted heart morphology and outcome. ACR occurs most commonly and is characterized by the presence of inflammatory cells in the myocardium, with diagnosis being significantly dependent from pathohistological examination results. The therapy still remains mainly empirical. ACR has been described precisely, and the advent of immunosuppressants significantly lowered its frequency. This paper describes such a clinical case in one of our patients with the review of contemporary criteria for diagnosis as well as treatment options focusing at existing limitations and need for further studies and innovations. Clinical efforts in managing the patients after heart transplantation include three basic goals: prevention of rejection, prevention of infectious complications and minimization of potential side effects of immunosuppressive therapy. Today the diagnosis of rejection strongly depends on pathomorphologic findings of EMB. However, up-to-date methods of cardiovascular visualization, namely EchoCG with TDI and STE and cardiovascular MRI, are also a valuable instrument for diagnosis. These investigations allow for high suspicion of heart transplant rejection earlier than EMB or in case it is not available, which was demonstrated in the described clinical case. For now management of such patients remains mainly empirical, and we hope that advances in molecular biology will help us to improve our capabilities in managing such patients.